(untitled) (Economics and region, 2023)
In wartime, hotels often suffer significant losses and difficulties in doing business. The war leads to a decrease in the tourist flow, limits the mobility of people and worsens the economic situation in the country, which leads to a drop in the popularity and profitability of hotels. In such situations, hoteliers are often forced to take measures to adapt to the uncertain situation. Some possible strategies include lowering prices, reorganizing or reducing staff, attracting new customers with special offers and promotions. It is taken into account that when analyzing the impact of the war on the hotel sector of Ukraine, such aspects as the destruction of infrastructure, the closure or annexation of enterprises in the occupied territories, the withdrawal of hotels in the occupied territories from the international market, the emigration of qualified personnel due to reduction or mobilization, the reduction or disappearance of consumers of hotel services, transition to the "military hotels" category or change of their purpose, etc. negative impact, such as lack of investment, slowdown of economic activity in the hotel market. In such conditions, hotels may experience physical damage and destruction due to shelling or military operations. In addition, the reduced demand for hotel services due to the dangerous situation can lead to great financial difficulties for hotels. The business model of the hotel industry, which is based on stability and security, is disrupted during the war period, which leads to a significant decrease in the activity and profits of hotels. To attract investors to the hotel industry during wartime, instruments such as tax incentives and reduction of the tax burden on investors can be used. Financing the hotel industry in Ukraine during a war becomes a difficult task, as conflict situations usually lead to a decrease in tourist flow and economic instability. Also, possible options for development during martial law may be targeting the local market and cooperation with military, humanitarian organizations or providing services to frontline workers. It is important to note that hotel development in wartime is a powerful challenge and requires a creative and strategic approach to survive and maintain business.